2022
DOI: 10.3390/md20010050
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombotic Activity of Heparinoid G2 and Its Derivatives from the Clam Coelomactra antiquata

Abstract: Clam heparinoid G2 (60.25 kDa) and its depolymerized derivatives DG1 (24.48 kDa) and DG2 (6.75 kDa) prepared from Coelomactra antiquata have been documented to have excellent fibrinolytic and anticoagulant activity. In this study, to further explore the antithrombotic activity of G2, DG1 and DG2, azure A, sheep plasma, and clot lytic rate assays were used to determine their anticoagulant and thrombolytic activity in vitro. The results indicated that the anticoagulant titer of G2 was approximately 70% that of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…G2 is prepared by using the extraction of G15 as a reference, and DG1 is a low molecular weight fragment of the vitamin-catalysed free-radical depolymerisation of G2. In a previous study, in a mice blacktail model, we found that gavage of equal doses of DG1, G2, and heparin sodium had a comparable ability to reduce the blacktail ratio in mice [9].…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…G2 is prepared by using the extraction of G15 as a reference, and DG1 is a low molecular weight fragment of the vitamin-catalysed free-radical depolymerisation of G2. In a previous study, in a mice blacktail model, we found that gavage of equal doses of DG1, G2, and heparin sodium had a comparable ability to reduce the blacktail ratio in mice [9].…”
Section: Introductionmentioning
confidence: 75%
“…Low molecular weight clam heparinoid DG1 with a molecular weight of 24.48 kDa are derived from vitamin catalytic free-radical depolymerisation of native clam heparinoid G2. We chose DG1 to prepare oral antithrombotic nanoparticles because of its strong oral antithrombotic activity and low molecular weight [9]. In this study, we analysed physicochemical properties that impact the preparation of DG1 nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…Heparin therapy includes a number of adverse effects, such as bleeding and thrombocytopenia in contrast to the possibility of infectious organism contamination, which restricts its use reported by Chen et al . (2022). When working with polysaccharides, anticoagulant action is constantly taken into account.…”
Section: Functional Properties Of Sccmentioning
confidence: 99%
“…The anticoagulant medication mammalian-derived heparin, which is generated from swine intestinal and bovine lung, both protects and cures thromboembolic illness. Heparin therapy includes a number of adverse effects, such as bleeding and thrombocytopenia in contrast to the possibility of infectious organism contamination, which restricts its use reported by Chen et al (2022). When working with polysaccharides, anticoagulant action is constantly taken into account.…”
Section: Anticoagulant Activitymentioning
confidence: 99%